Foliar Application of Salicylic Acid Improves Water Stress Tolerance in Conocarpus erectus L. and Populus deltoides L. Saplings: Evidence from Morphological, Physiological, and Biochemical Changes - Zikria Zafar; Fahad Rasheed; Rana Muhammad Atif; Muhammad Asif Javed; Muhammad Maqsood; Oliver Gailing (Plants, 2021)
Reforestation efforts are being challenged as water stress is hampering the sapling growth and survival in arid to semiarid regions. A controlled experiment was conducted to evaluate the effect of foliar application of salicylic acid (SA) on water stress tolerance of Conocarpus erectus and Populus deltoides. Saplings were watered at 90%, 60%, and 30% of field capacity (FC), and half of the saplings under 60% and 30% FC were sprayed with 1.0 mM SA. Results indicated that dry weight production decreased significantly in Populus deltoides under both water deficit conditions, and leaf gas exchange parameters decreased significantly in both the species under both soil water deficit conditions. Foliar application of SA resulted in a significant increase in leaf gas exchange parameters, and compatible solutes, thereby increasing the dry weight production in both of the species under soil water deficit. Oxidative stress (hydrogen peroxide and superoxide anions) increased under soil water deficit and decreased after the foliar application of SA and was parallel to the increased antioxidant enzymes activity (superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase). Therefore, it can be concluded that foliar application of 1.0 mM SA can significantly improve the water stress tolerance in both species, however, positive impacts of SA application were higher in Conocarpus erectus due to improved photosynthetic capacity and increased antioxidant enzyme activity.